Effectiveness Analysis of Nadine Implementation at Indonesia’s MoF: A Combined Approach Using Importance-Performance Analysis and Causal Relationship Analysis - Dara, Despinur; Putra, Donny Maha (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2025)
Research Originality — This study provides a unique empirical examination of technology acceptance within Indonesia's public administration system. Unlike previous research, which often focuses on developed countries, this study addresses a gap by analyzing challenges and strategies specific to a developing nation. It contributes to the innovation diffusion theory and the unified theory of acceptance and use of technology (UTAUT) by offering real-world data on the adoption of a digital system within a government institution. Research Objectives — To evaluate the effectiveness of the NADINE (Digital Official Script System) application implemented by Indonesia's Ministry of Finance (MOF). Specifically, it investigates user satisfaction, identifies areas for improvement, and explores the relationship between policy success and the Application's performance. Research Methods — A quantitative survey approach is employed, collecting data from over 2,500 MOF employees. Importance-performance analysis is used to assess user satisfaction and prioritize key areas for improvement. Correlation and regression analyses examine the relationship between policy success and the Application's effectiveness. Additionally, a word cloud analysis is conducted to extract insights from user feedback. Empirical Results — Findings indicate high user satisfaction with both the Policy and the NADINE application. Despite the positive reception, areas such as user interface and navigation require improvement. A strong positive correlation is observed, demonstrating a close link between policy effectiveness and application performance. Regression analysis further confirms this influence, suggesting that improvements in the Application can enhance policy outcomes. Implications — The study highlights the importance of relative advantage, compatibility, and ease of use in user acceptance of digital government systems. Key recommendations include enhancing user training and optimizing the user interface to improve the overall user experience. These findings provide valuable insights for policymakers and system developers in designing and implementing digital solutions in public administration, particularly in developing country contexts.